Akutni abdomen - Tomažič, Aleš (Medicinski razgledi, 2011)
The term acute abdomen refers to signs and symptoms of abdominal pain, tenderness, nausea and vomiting, with or without the signs oflocal or diffuse peritonitis and systemic ilness, a clinical presentation, that of ten requiresemergency surgical therapy. This review provides a framework for understanding abdominal pain, so that practitioners may determine those patients who need a more expedited evaluation. In the first part of the article, a general approach to the patient is outlined. Details in clinical examination and diagnostic possibilities are highlighted aswell. The pathways ofvisceral and somatic pain are described and signs of peritonitis are listed.From among diagnostic methods, laboratory tests, ultrasound and computer tomography are the most important ones for determining the reason of acute abdomen. The second part of the article describes the most frequent causes of acute surgical abdomen: peritonitis, ileus, bleeding, acute mesenteric ischemia, cholecystitis, peptic ulcer perforation, acute pancreatitis, appendicitis and diverticulitis.
Keywords: Abdomen, Acute; Trebuh, akutni; Trebušni absces; Etiology; Črevesna obstrukcija; Diagnosis; Trebušna bolečina; Therapy; Abdominal Pain; Mezenterična žila, okluzija; Abdominal Abscess; Žolčni kamni; Peritonitis; Pankreatitis; Krvavitev; Intestinal Obstruction; Hemorrhage; Peptični ulkus, perforacija; trebuh; Mesenteric Vascular Occlusion; bolečina; Cholecystitis; Cholelithiasis; akutni abdomen; kirurško zdravljenje; Peptic Ulcer Perforation; Pancreatitis; Appendicitis; Holecistitis; Apendicitis; diagnostika